2020
DOI: 10.1038/s41598-020-72772-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of musical pleasure and musical hedonia on verbal episodic memory

Abstract: Music listening is one of the most pleasurable activities in our life. As a rewarding stimulus, pleasant music could induce long-term memory improvements for the items encoded in close temporal proximity. In the present study, we behaviourally investigated (1) whether musical pleasure and musical hedonia enhance verbal episodic memory, and (2) whether such enhancement takes place even when the pleasant stimulus is not present during the encoding. Participants (N = 100) were asked to encode words presented in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 94 publications
2
23
0
1
Order By: Relevance
“…No significant differences were found for the other subjective ratings, namely, emotional valence and top‐ten ratings ( P’ s > 0.118). These findings are consistent with previous studies showing a link between pleasure and memory formation 25,47 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…No significant differences were found for the other subjective ratings, namely, emotional valence and top‐ten ratings ( P’ s > 0.118). These findings are consistent with previous studies showing a link between pleasure and memory formation 25,47 …”
Section: Resultssupporting
confidence: 93%
“…Notably, and in line with this literature, our findings suggest that the drug manipulation differentially modulated participants' performance as a function of their sensitivity to musical reward. Under levodopa, there is a trend toward greater reward‐potentiated effects on music in individuals with lower music reward sensitivity, who generally show poorer reward–memory effects 25,47 and reduced engagement of dopaminergic circuits while listening to music 14 . Thus, only individuals with low sensitivity to music benefited from the increase in dopaminergic transmission, while performance in music hedonic individuals was disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, performance in the R2 and R4 repetition lags approached ceiling, which may have masked differences between neurostimulation conditions. Although some research has examined the effects of listening to autobiographically-salient music on subsequent episodic memory in younger adults 7 , 9 , this finding in healthy older adults is limited to one pilot study that found no change in verbal episodic memory after listening to non-preferred or preferred music 74 . Studies have examined episodic memory performance in older adults in the presence of concurrent background music during encoding or retrieval stages 6 , 75 , 76 , but it is unclear whether the observed changes are attributed to the arousal-and-mood hypothesis or some other attentional mechanism 1 , 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Research into the arousal-and-mood hypothesis has suggested that listening to enjoyable music can heighten arousal and induce positive affect, thereby influencing subsequent cognitive performance 1 , 2 . In older adults, benefits following music listening were shown in various cognitive domains such as autobiographical memory recall 3 , working memory 4 , semantic fluency 5 , semantic memory 6 , and episodic memory 7 9 . Given individual differences in musical listening preferences and distastes, autobiographically-salient music may be of particular interest in subsequently eliciting cognitive benefits following music listening.…”
Section: Introductionmentioning
confidence: 99%
“…There is, indeed, direct evidence not only for the causal role of dopamine in pleasure response when listening to music as compared to highly rewarding hedonic experiences, but also for the stimulation of oxytocin and the consequent inducement of prosocial behavior [38][39][40][41]. Neuroimaging, neuropsychological and brain stimulation studies in musical anhedonia (the inability to find music pleasurable) also seem to suggest that human appreciation of music emerges from the predictive process of auditory perception, which connects to the structures involved in the brain's dopaminergic reward system, to the extent that it may function as a stimulus for verbal episodic memory and learning [42][43][44].…”
Section: Music-language Universality and The Biocultural Origins Of Musicmentioning
confidence: 99%